Analisis Kebijakan Pemerintah Daerah dalam Mendorong Kesejahteraan Keluarga di Kabupaten Sleman (Studi Kasus Konsep Keluarga Sakinah pada Pasangan Karir) - Putri, Anggraini Monica; Elza Qorina Pangesti (STAI Bumi Silampari, 2025)
Humans are created as social creatures, and need others to sail the ark of life. One way to navigate life is to go through marriage. This study aims to analyze the policies of the Sleman Regency Regional Government in encouraging family welfare, focusing on the concept of the sakinah family in career couples. The phenomenon of increasing the number of career families poses challenges in maintaining household harmony in the midst of busy work. This type of research is sociological law (juridical-empirical). The case study approach is used to provide a holistic and in-depth understanding of the specific phenomena that occur at the research site. The results of the study show that local governments have implemented various policies and programs that support the realization of family welfare, including through the development of the Sakinah family, economic empowerment, religious activities, and community institutional support. However, career couples still face obstacles in the form of limited interaction time, women's double burden, and the influence of the modern social environment. Nevertheless, the application of religious values, openness, mutual respect, honesty, and gratitude have proven to be the main factors that strengthen the concept of the sakinah family in the career family. This research emphasizes that collaboration between regional policies and the resilience of community religious values is the key to realizing a prosperous sakinah family in Sleman Regency.